Steroid hormones as interkingdom signaling molecules: Innate immune function and microbial colonization modulation - Michael W Patt; Lisa Conte; Mary Blaha; Balbina J Plotkin (AIMS Molecular Science, 2018)
Steroid hormones e.g., estrogen, progesterone, testosterone and dehydroepiandosterone, act as inter-kingdom quorum chemical signaling compounds. All steroids examined exhibit a steroid concentration specific bi-functionality. At one end of the spectrum, the steroids enhance expression of virulence-associated behaviors, most specifically, increased rate of replication and adherence to surfaces. In contrast, the hormones also function as innate immune system compounds providing first-line protection against essential pathogen behaviors e.g., biofilm formation, which plays a role in initiation of the vast majority of infectious processes, especially chronic infections. Mechanistically, this protection is mediated by both direct effects of steroids on microbes, as well as indirect actions which result in expression of nitric oxide at levels reported to inhibit proper biofilm formation and cause return of sessile cells to a planktonic state.